Nigerian Enterprises Promotion decree, 1977 : promotion of Nigerian enterprises - Nigerian Enterprises Promotion Board (Lagos : The Board, 1977)
The book contains guidelines under which Nigeria enterprises will be promoted in lines with the 1977 Nigerian enterprises promotion decree.
asm; 13/02/19
Loans
Keywords: Business enterprises; Investments; Joint ventures